Tourism Bike Tracking Design with The LoRaWAN Network Approach to The Meikarta Central Park Area - Legenda Prameswono Pratama; Mauludi Manfaluthy; Feri Nugroho; Anindya Ananda Hapsari; Koko; Safaa Najah Saud Al-Humairi (Teknika, 2025)
Technological developments in Indonesia are relatively rapid, and most people have become part of the Internet of Things era. There are a couple of new technologies in the Internet of Things, one of which uses long-range (LoRa) communication technology, a wireless delivery method using radio signals at a frequency of 433 MHz. Meikarta Central Park is a city park that provides tourist bicycle rentals. Problems often occur when visitors rent bicycles, resulting in tourist bicycles being lost or placed incorrectly. All these problems make it difficult for operators to find abandoned bicycle locations. This research develops a system to detect the location of Meikarta’s tourist bicycles using a GPS tracker with an Arduino microcontroller based on a long-range working principle. On the other hand, the location point can be seen on the map’s application so that the whereabouts of the bicycle can be known. The research results of the tracking from the tourist bicycle GPS tracker using LoRa were 5 test locations, the furthest range of 625 meters on the first tourist bicycle with an accuracy value of 11.2 meters. Meanwhile, the second tourist bike has the most extended range of 590 meters with an accuracy level of 4.4 meters.